Diversity and conversation status of Mammals in Wang Kelian State Park, Perlis, Malaysia - Vijaya Kumaran Jayaraj; Siti Hajjar Muhamad Daud; Mohd Isham Azhar; Shahrul Anuar Mohd Sah; Seri Intan Mokhtar; Mohd Tajuddin Abdullah (2013)
A series of surveys in Wang Kelian State Park, Perlis were carried out since 2009 to 2011 to document the diversity of mammals. Two sampling stations; 1) the Wang Burma cave trail and 2) the Orchard leading to Tasik Meranti were sampled for small mammals using mist-nets, harp traps, cage traps and were accounted through direct observation. The highlight of this study includes new geographic records for Rhinolophus chiewkweeae and Rousettus leschenaultii for the state of Perlis. Additionally, there were also 30 new distributional records of mammals in this protected area, increasing the total known mammals of Wang Kelian State Park to 86 species. Although having poorly known mammals such as R. chiewkweeae and Macaca arctoides in this park, the diversity of mammals in Wang Kelian State Park is still underestimated as the species cumulative curve over time has yet to reach a stationary phase. In conclusion more surveys need to be done especially the northern part of the park near the Malaysia-Thailand border and Tasik Meranti in order to look at possible occurrences of threatened mammals highlighted in this study.